Impact of Patient Education on Establishing Trust as the Medical Student Provider: A Student Run Free Clinic Experience - David Salchert; Marley Lee; Chandler Hinson; Richard A Perkins; Stephanie Rudolf (Journal of Student-Run Clinics, 2024)
Background: Effective doctor-patient relationships are crucial for quality healthcare, and trust is central to this dynamic. Trust in healthcare comprises competence, empathy, communication, and shared decision-making. Patient education sessions offer a platform to enhance patient trust, especially amongst novice providers. This study investigates the impact of patient education sessions led by medical students on patient trust within the context of a student-run free clinic.Methods: At our student-run free clinic, we conducted a cross-sectional survey to collect patient data, including background information, trust in healthcare, and opinions on education sessions at a student-run free clinic.Results: Amongst the enrolled 24 participants, the demographics revealed a diverse racial composition, with a significant portion having not completed high school and the majority being either unemployed or on disability. Following attendance at patient education sessions, a high percentage of participants reported positive experiences, including improved rapport with medical student providers and a likelihood of returning for future services and following medication recommendations.Conclusion: This study highlights the significant role of patient education sessions in fostering trust between patients and providers, improving health behaviors, and enhancing the broader healthcare system's credibility. It demonstrates how such sessions empower patients, leading to better medication adherence and timely medical assistance seeking, while also suggesting their potential for implementation across various healthcare settings to improve patient engagement and healthcare services.